TEXT AS REFLECTED IN CLASSROOM INTERACTION - Puspa Indah Ramadhani; Berlin Sibarani (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This study was aimed at describing the ways of the teachers in teaching readingcomprehension of recount text taught in grade eighth and finding out the reason why theteachers did that ways in teaching. This study employed a qualitative research design thattaken from two English teachers, the first was from SMP Swasta Muhammadiyah 05Medan, and the second was from SMP N 37 Medan. The data were collected by usingpassive participant observation with the tape and video records as a tool to record theinteraction and interview to find the reason why the teachers did that way in teachingreading comprehension of recount text. The data were analyzed by using three majorphases of analysis: data reduction, data display, and conclusion drawing (Miles,Huberman, and Saldana: 2014). This study revealed that the teachers used the threereading stages as it is applied into scientific approach in teaching reading comprehensionof recount text: (a) pre-reading: asking students’ background knowledge about the topic,asking to open the books and explaining the content about the genre of recount text; (b)while-reading: asking the student to read the text on the text book, recalling students’knowledge about recount text, managing the classroom to do a group task in answeringthe questions based on the recount text, and; (c) post-reading: guiding the students toanswer the questions and clarifying the answer together. It also found that in theclassroom interaction the teachers took their role very good in order to lead the classroomactivity while teaching. The reason underlying why the teachers did those ways becauseteachers believed that by giving the students the genre knowledge of recount text can helpthe student to understand and recognize the recount text; the student will not be engagedby reading text activity if they just asked to read the text; the information about genreknowledge of recount text can help the students in reading comprehension of recount text,and; the competence of the students in mastering the reading recount text can be seenfrom answering the questions related to the text by doing reading comprehension.